2020
DOI: 10.1063/5.0029167
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of three-dimensional domain wall arrangement in ferroelectric K0.9Na0.1NbO3 epitaxial thin films

Abstract: The three-dimensional arrangement and orientation of domain walls in ferroelectric K 0.9 Na 0.1 NbO 3 /(110)NdScO 3 epitaxial thin films were investigated at different temperatures both experimentally by means of piezoresponse force microscopy and three-dimensional x-ray diffraction and theoretically by three-dimensional phase-field simulations. At room temperature, a well-ordered herringbone-like domain pattern appears in which there is a periodic arrangement of a 1 a 2 /M C monoclinic phases. Four different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Typically, such patterns are characterized using synchrotron-based 3D-RSM. [17][18][19] When we rotate the sample ϕ = 45 ○ away from the NSO[-110] direction, we can still observe off Bragg scattering peaks from the domains. However, they appear at different positions, clearly indicating that at this rotation angle, they do not originate from scattering in the diffraction plane.…”
Section: Articlementioning
confidence: 99%
“…Typically, such patterns are characterized using synchrotron-based 3D-RSM. [17][18][19] When we rotate the sample ϕ = 45 ○ away from the NSO[-110] direction, we can still observe off Bragg scattering peaks from the domains. However, they appear at different positions, clearly indicating that at this rotation angle, they do not originate from scattering in the diffraction plane.…”
Section: Articlementioning
confidence: 99%
“…It is mainly because the distribution of X-ray diffraction intensity from a multi-domain crystal may be as complex as the domain patterns themselves. Up until now, single-crystal X-ray diffraction was successfully applied for characterization of domains in epitaxial thin films (Ehara et al, 2017;Braun et al, 2018;von Helden et al, 2018;Lee et al, 2019Lee et al, , 2020Schmidbauer et al, 2020) where possible domain patterns are greatly limited by the constraints imposed by the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been shown that the domain wall orientation in the herringbone-like domains varies with respect to the chemical composition [46] . Despite these effort s, it is still challenging to realize and understand the three-dimensional arrangement of the superdomains solely from experimental characterization [47] . The configuration of ferroelectric polarization in the superdomains, particularly near the superdomain boundaries, is not well understood.…”
Section: Introductionmentioning
confidence: 99%